Advancements in Forensic Support Devices: The Interdisciplinary Role of Technicians in Postmortem Care and Evidence Preservation - Alshammari, Talal Mohammed; Alshammari, Yousef Faris Mubarak; Alshammari, ‏Lafi Jahhad Juaan; Alshammary, Ahmad Awwad Khalaf; Alshammary, Mansour Salfig; Marzouq, Meshal Nashmi; M, Alshammar, Adel Dhaher; Almohifer, Khalid Naseer (Journal of Posthumanism, 2024)
Introduction: The landscape of forensic science has witnessed remarkable technological advancements in recent years, profoundly impacting the role of forensic technicians in postmortem care and evidence preservation. Aim of work: To explore the latest developments in forensic support devices and highlights the interdisciplinary contributions of technicians, emphasizing how emerging technologies enhance the accuracy, efficiency, and reliability of forensic investigations.Methods: We conducted a comprehensive search in the MEDLINE database's electronic literature using the following search terms: Advancements, Forensic, Support Devices, Interdisciplinary, Role, Technicians, Postmortem Care and Evidence Preservation. The search was restricted to publications from 2011 to 2023 in order to locate relevant content. We performed a search on Google Scholar to locate and examine academic papers that pertain to my subject matter. The selection of articles was impacted by certain criteria for inclusion.Results: The publications analyzed in this study encompassed from 2011 to 2023. The study was structured into various sections with specific headings in the discussion section.Conclusion: The advancements in forensic support devices have transformed the field of forensic science, enhancing the capabilities of technicians in postmortem care and evidence preservation. The integration of AI, mobile and IoT forensics, next-generation DNA sequencing, and biometric technologies underscores the interdisciplinary nature of modern forensic work. Technicians are now essential contributors to forensic investigations, requiring a blend of technical expertise, scientific knowledge, and ethical awareness. As technology continues to evolve, ongoing training and collaboration across disciplines will be vital to harness these innovations effectively and uphold the integrity of forensic science.